Infertility and Psychological Well-Being: The Interplay of Post-Traumatic Growth and Affective Personality Types in Infertile Lebanese Muslim Women - Fatin Khalifeh; Anastasia Salame; Ghina Ghazeeri (Mental Illness)
The study is aimed at exploring the influence of affect and personality types among Lebanese women undergoing in vitro fertilisation (IVF) on achieving positive psychological growth. It specifically focused on predicting post-traumatic growth and its correlation with positive and negative affect, as well as affective personality type (APT). Employing a cross-sectional quantitative survey, the research involved 106 participants from one fertility centre undergoing IVF. The participants’ APTs were categorised into “self-actualising,” “high-affective,” “low-affective,” and “self-destructive” based on their positive and negative affect. The findings indicated a noteworthy positive correlation between post-traumatic growth and variables such as household income, educational level, and employment. Hierarchical multiple regression analysis identified positive and negative affect as significant predictors of self-reported post-traumatic growth scores. Additionally, the study highlighted the significance of self-actualising and high-APTs in predicting post-traumatic growth. The conclusion suggested that healthcare professionals should consider the positive and negative affect, as well as APTs of infertile patients, to provide effective support and facilitate their emotional well-being during infertility treatments.